Defining the Influence of Age and Gender on Key Performance Metrics in Badminton - Pambudi, Titis; Sugiyanto, FX; Tomoliyus, Tomoliyus; Ilham, Ilham; Orhan, Bekir Erhan; Geantă, Vlad Adrian (Physical Education Theory and Methodology, 2025)
Background. Badminton, a racquet sport that has gained global popularity, demands technical precision, tactical awareness, and exceptional physical fitness. Skills such as smashing, footwork, and minimizing errors are critical to success. However, the specific influence of age and gender on these metrics, especially among younger players, remains underexplored. Objectives. This study aimed to examine the effect of age and gender on key badminton performance metrics, including smash ability, footwork, and unforced errors, in order to identify developmental and demographic factors influencing skill acquisition and execution. Materials and methods. A quantitative descriptive study involved 24 athletes (aged 9–14) from the Wincorp badminton organization in Surakarta, Indonesia. Participants were grouped by age (9–10, 11–12, 13–14 years) and gender, ensuring equal representation. Over two months, data on smashing, lobbing, driving, footwork, and error rates were collected. Descriptive statistics and MANOVA analyzed differences, with a significance level set at p < 0.05. Results. MANOVA revealed significant age-related effects on smashing (p = 0.000), footwork (p = 0.000), and error points (p = 0.000), with beginners (13–14 years) excelling in most metrics. Gender differences were also found to be substantial for smashing (p = 0.000), footwork (p = 0.000), and error points (p = 0.003), with males outperforming females in most categories. Interaction effects between age and gender were significant for smashing and footwork (p < 0.05). However, no considerable differences were observed for netting and serving strokes across age or gender. Conclusions. The study indicates that age and gender significantly influence badminton performance metrics. Beginner athletes (13–14 years) demonstrated superior skills compared to younger groups, while males generally outperformed females. These findings highlight the importance of tailoring training programs by age and gender to optimize skill development and reduce performance gaps. Further studies should be performed to investigate biomechanical and psychological factors to refine coaching strategies.